PENGARUH INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP KUALITAS PEMERIKSA STUDI PADA BADAN PEMERIKSA KEUANGAN PERWAKILAN PROVINSI RIAU - Ari Syahputra Ladisura; Andreas -; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to analyze the effect of intellectual and emotional intelligent towards auditor’s quality at Financial Investigation Bureau of Indonesia for Riau Province Reserve. Data in this research were collected using a survey method with help of research instruments such as questionnaires were distributed to 40 auditors who works at the Financial Investigation Bureau of Indonesia for Riau Province Reserve. Data in this research will be analyzed using multiple linear regression using SPSS 18 software. To test the validity and reliability of research instrument used pearson correlation and cronbach alpha. Besides it is also testing data for normality using a normal probability plot. There are several findings in this research, first all instruments used in this research was reliable and valid. Second, distribution of respondents was normal. Third, educational qualification, professional qualification, independency, self-awareness, self-controlling, and empathy, were affected significantly the auditor’s quality, while experience, motivation, and social skill were not affected the auditor’s quality of Financial Investigation Bureau of Indonesia for Riau Province Reserve. Keywords: Intellectual, Emotional Intelligence, and Auditor’s Quality